NEW EA TYPE VARIABLE STAR IN THE FIELD OF NGC 2174 AND NGC 2175 - Bryukhanov, I. S. (Одеські астрономічні публікації, 2017)
New Algol-type star is found with α = 06h09m16s.9, δ = +20°25’06’’ (2000.0), JD Min= 2449311.467 + 2.210345 x E, range 13m.9 - 15m.3, duration of eclipse D = 0.07.